Between Divinity and Dullness: The Advent of Personal Computers in Italian Literature - Lima, Eleonora (Quaderni d'Italianistica, 2020)
This article examines the cultural impact of personal computers in Italian literature in the first decade of their mass diffusion (from the mid-1980s to the second half of the 1990s) through the analysis of four texts written by some of the most respected writers of the time: Primo Levi’s article “Personal Golem” (1985), Umberto Eco’s novel Il pendolo di Foucault (1988), Francesco Leonetti’s novel Piedi in cerca di cibo (1995), and Daniele Del Giudice’s story “Evil Live” (1997). More than simply addressing the advent of personal computers, what these texts have in common is the use of religious images and metaphors in order to make sense of the new technology. This study aims at showing how this frame of reference served the four writers in expressing the contradictions inherent to the machine. Bulky and tangible because of its hardware, but animated by an elusive and mysterious software, the personal computer was perceived at the same time as a dull office appliance and a threatening virtual entity. Finally, by showing how timely and well-informed these literary works on the impact of PCs are, this article wants to make the case for considering the role of literature in shaping computer culture.